The Link and Effect of Leadership Style on Teacher Organizational Commitment in South Ethiopia: A Case of Wolaita Zone - Mulatu Dea Lerra (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
This study was conducted with the objective ofassessing the link and effect of leadership style on teachers’ commitment in secondary schools in WolaitaZone, SNNPR.To this end, descriptive survey method was used. Simple random and purposive sampling techniques were used to select sample respondentsfrom each sample school of seven woredas and two city administrations.Questionnaires were preparedand administered to 128principals and vice principals.Quantitative datawas collected by using survey tools. The quantitative data were analysed using inferential statistical techniques such as correlation and regression analyses. The study revealed that there was positive correlation between transformational leadership and teachers’commitment. In addition, leadership style was found to have positive and significant impact on techers’ commitment. However, there was negative correlation between laissez-faire leadership style and teachers’ commitment. It was recommended that combination of both transformational and transactional leadership attributes should be used in order to bring about positive influence on teachers’ commitment. Also,to motivate workers, school leadership should use appropriate strategies in the form of giving recognitions to their better job, arranging short training, promoting experience sharing culture among them, and providing various supports that might help to develop their self-confidence and build team-spirit in creating a positive relationship.